Optimizing student learning in Computer Numerical Control subject: A comprehensive analysis of influential factors - Fadri, Muhammad Al; A, Yufrizal; Fernanda, Yolli; Prasetya, Febri (Journal of Engineering Researcher and Lecturer, 2023)
The learning outcomes achieved by students are influenced by many factors. This study aims to determine the level of support of factors (motivation, interest, family, teacher's role, learning methods and learning facilities) that influence the learning process in achieving student learning outcomes in CNC learning in class XI. The subjects in the study were Class XI students majoring in Mechanical Engineering at SMK Negeri 5 Padang in the 2022/2023 academic year totalling 37 people. Because the number of research subjects (population) is less than 100 people, so all of them are taken as samples or total sampling. Data collection was carried out using observation, questionnaires and documentation. Data analysis techniques using descriptive statistical techniques. From the data analysis, it shows that of each factor studied, the learning facility factor has the lowest level of support for student academic success compared to other factors that have been studied by researchers. Therefore, learning facilities at SMK Negeri 5 Padang in CNC subjects need to be improved again to support the student learning process and achieve better learning achievements for students.